2022
DOI: 10.3389/fmars.2022.1029360
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaf extract improves non-specific immunity and antioxidant capacity of largemouth bass (Micropterus salmoides) fed a high-starch diet

Abstract: A 70-day experiment was conducted to investigate the effects of mulberry leaf extract (MLE) on growth, proximate compositions, antioxidant and plasma biochemical parameters, and indices of non-specific immunity of largemouth bass (Micropterus salmoides) fed a high-starch diet. Two hundred eighty largemouth bass (initial body weight, 68.00 ± 0.19 g) were randomly fed seven diets: basal-starch diet (BSD; 8.88% starch), high-starch diet (HSD; 11.42% starch), and HSD diets supplemented with 0.05%, 0.10%, 0.20%, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The results of this experiment showed that ELM can increase the CAT activity, GSH content, and T-AOC in the liver, and reduce the MDA content in the liver. The results of this experiment are consistent with previous findings that ELM increased CAT activity and T-AOC in liver tissue of largemouth bass and decreased MDA content in liver [ 20 ]. The above results indicated that ELM can remove reactive oxygen species in the liver by increasing CAT activity and GSH content in the liver of spotted sea bass, thereby increasing the antioxidant capacity of the liver.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this experiment showed that ELM can increase the CAT activity, GSH content, and T-AOC in the liver, and reduce the MDA content in the liver. The results of this experiment are consistent with previous findings that ELM increased CAT activity and T-AOC in liver tissue of largemouth bass and decreased MDA content in liver [ 20 ]. The above results indicated that ELM can remove reactive oxygen species in the liver by increasing CAT activity and GSH content in the liver of spotted sea bass, thereby increasing the antioxidant capacity of the liver.…”
Section: Discussionsupporting
confidence: 92%
“…And 2–8 g/kg ELM can improve the muscle quality of African catfish and increase the antioxidant capacity of feed [ 19 ]. Some studies have also found that adding 1–10 g/kg ELM to high-carbohydrate feed can improve the antioxidant capacity, immunity, and glycolipid metabolism of largemouth bass [ 20 ]. However, the effect of ELM on the liver of sea bass has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The ELM increased the SOD activity and GSH level in the intestinal of the spotted sea bass, and decreased the content of MDA in the intestinal tract of the spotted sea bass, but not significantly. And studies have shown that ELM can increase the activity of CAT and reduce the content of MDA in largemouth bass (Tingsen et al, 2022). Adding mulberry leaf powder to the feed can increase the GSH content of tilapia (Miao et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…In recent years, there has been an increasing interest in the research of the immunomodulatory effects of herbal extract on M. salmoides. It has been discovered that lots of herbal products such as sweet wormwood (Artemisia annua) extract [8], hardy rubber tree (Eucommia ulmoides Oliver) extract [9], mulberry leaf (Morus alba) extract [10] and Yinchenhao (Artemisiae Scopariae) decoction [11] positively regulated liver antioxidant capacities and mitigated impairments of immunity in M. salmoides, displaying the potential of herbal products as dietary immunopotentiators.…”
Section: Introductionmentioning
confidence: 99%